2016
DOI: 10.1371/journal.pone.0159741
|View full text |Cite
|
Sign up to set email alerts
|

Anticipation of Monetary Reward Can Attenuate the Vigilance Decrement

Abstract: Motivation and reward can have differential effects on separate aspects of sustained attention. We previously demonstrated that continuous reward/punishment throughout a sustained attention task improves overall performance, but not vigilance decrements. One interpretation of these findings is that vigilance decrements are due to resource depletion, which is not overcome by increasing overall motivation. However, an alternative explanation is that as one performs a continuously rewarded task there are less pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
45
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 48 publications
8
45
0
Order By: Relevance
“…These sustained influences of motivation are coupled with modulations of the transient signals evoked by reward-related stimuli and tasks (Jimura et al, 2010;Pessoa & Engelmann, 2010), mirroring the just described benefits observed for reward-associated stimuli (e.g., Kiss et al, 2009;Serences, 2008). One interpretation of these findings is that such motivation effects reflect volitional adjustments in task engagement, resulting in attention being better focused on task-related stimuli (e.g., Esterman et al, 2016;Esterman, Poole, Liu, & DeGutis, 2017;Esterman, Reagan, Liu, Turner, & DeGutis, 2014).…”
Section: Automaticity and Associative Learningmentioning
confidence: 60%
“…These sustained influences of motivation are coupled with modulations of the transient signals evoked by reward-related stimuli and tasks (Jimura et al, 2010;Pessoa & Engelmann, 2010), mirroring the just described benefits observed for reward-associated stimuli (e.g., Kiss et al, 2009;Serences, 2008). One interpretation of these findings is that such motivation effects reflect volitional adjustments in task engagement, resulting in attention being better focused on task-related stimuli (e.g., Esterman et al, 2016;Esterman, Poole, Liu, & DeGutis, 2017;Esterman, Reagan, Liu, Turner, & DeGutis, 2014).…”
Section: Automaticity and Associative Learningmentioning
confidence: 60%
“…The results of recent studies have produced findings that are difficult for either theory to fully explain. As noted by Thompson et al,27 findings that increasing task engagement can improve performance on some tasks despite increasing task demands 28,29 and that self-reported mind wandering increases with time on task 21,30 are inconsistent with the resource-depletion account. In contrast, pure mindwandering accounts have difficulty accounting for reports 12,16 that vigilance tasks are stressful/effortful and that factors that increase attention to the task (e.g., displaying pleasant stimuli) either have no effect on or decrease sustained attention performance.…”
Section: Models Of Sustained Attentionmentioning
confidence: 94%
“…found that these typical reward manipulations increased overall performance (i.e., higher accuracy and lower response variability), while vigilance decrements in performance over time were unaffected. In order to keep overall task value constant, another study was completed where participants had the opportunity to gain a significant reward of $18 if they correctly withheld response to a specific target mountain scene. Results here showed that the typical vigilance decrement found in the previous study could be eliminated when the anticipated large reward was withheld until the end of the 10‐min run.…”
Section: Models Of Sustained Attentionmentioning
confidence: 99%
“…To achieve a better understanding of how stress and cognition interact to modulate the reward processes, it is necessary to determine how each of these factors per se influences motivation and hedonic experience. Previous research has focused on the complex relationship between cognition, motivation, and hedonic capacities (Akaishi & Hayden, ; Esterman et al, ; O'Connor, Rossiter, Yücel, Lubman, & Hester, ; Rothkirch, Schmack, Deserno, Darmohray, & Sterzer, ). A large body of research evidenced the effort‐discounting effect on reward valuation, so that the effort exerted to obtain a desired reward decreases as effort cost increases (for a review, see Kurniawan, ).…”
Section: Introductionmentioning
confidence: 99%